The representation of aspects of Afrikaner and British masculinity in the first season of Arende (1989) by Paul C Venter and Dirk de Villiers : a critical analysis - Van Eeden, Jeanne (University of Pretoria, 2014)
Dissertation (MA)--University of Pretoria, 2013.